2005
DOI: 10.1002/cncr.21590
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of lonafarnib, a farnesyl transferase inhibitor, in patients with chronic myeloid leukemia in the chronic or accelerated phase that is resistant or refractory to imatinib therapy

Abstract: BACKGROUNDLonafarnib (SCH66336) is a nonpeptidomimetic farnesyl transferase inhibitor that has demonstrated significant preclinical activity against chronic myelogenous leukemia (CML) cells and in CML animal models.METHODSIn the current study, the efficacy of lonafarnib was investigated in patients with CML in the chronic or accelerated phase that was resistant or intolerant to imatinib. Thirteen patients with CML in the chronic (n = 6 patients) or accelerated (n = 7 patients) phase were treated with lonafarni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 38 publications
1
33
0
2
Order By: Relevance
“…Lonafarnib, another farnesyl transferase inhibitor, showed efficacy in CML (93). Two responses were noted among 13 patients with CML in chronic or accelerated phase resistant to imatinib treated with lonafarnib (93).…”
Section: Other Potential Targets In CML Therapymentioning
confidence: 99%
“…Lonafarnib, another farnesyl transferase inhibitor, showed efficacy in CML (93). Two responses were noted among 13 patients with CML in chronic or accelerated phase resistant to imatinib treated with lonafarnib (93).…”
Section: Other Potential Targets In CML Therapymentioning
confidence: 99%
“…70 However, the results of a pilot study investigating lonafarnib in patients with imatinib-resistant CML have been discouraging with only 2 of 13 patients achieving a clinical response. 71 A recent report showed that lonafarnib is able to sensitize primitive, quiescent Bcr-Abl-positive progenitors to imatinib. 72 Recently, the FTI BMS-214662 was reported to enhance the cytotoxic effect of imatinib or dasatinib in primary CD34 + CML cells and significantly reduce the numbers of undivided primitive quiescent CML stem cells, either alone or in combination with imatinib or dasatinib.…”
Section: Lonafarnibmentioning
confidence: 99%
“…69 Ftase inhibitors (FTIs) inhibit farnesylation of a variety of proteins including RAS. 70 Although FTIs have shown only modest activity in CML as single agents, 71 the combination of imatinib with either tipifarnib 72 or lonafarnib 73 demonstrated significant clinical activity in phase I studies in imatinib-resistant CP CML, including in T315I-carrying patients. 72 A combination study of dasatinib and the FTI BMS214662, with 68-fold higher killing potency against quiescent (IC 50 0.7 mM) than proliferating (IC 50 47.5 mM) K562 cells, 74 is underway.…”
Section: Ras/raf Pathwaymentioning
confidence: 99%